2017
DOI: 10.17707/agricultforest.63.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Additive Main Effects and Multiplicative Interactions (Ammi) Analysis for Fresh Forage Yield in Common Vetch (Vicia Sativa L.) Genotypes

Abstract: SUMMARYThe study was held to evaluate genotype × environment interactions and stability status of twenty common vetch (Vicia sativa L.) genotypes in terms of fresh forage yield trait by using additive main effects and multiplicative interactions analysis (AMMI). Field trials of the study were carried out during 2008-09, 2009-10 and 2010-11 growing seasons under the rainfed conditions of two different locations of the Southeastern Anatolia region of Turkey. The field trials were established according to random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Sayar [29] evaluated genotype × environment interactions and stability of twenty common vetch (Vicia sativa L.) genotypes for fresh forage yield traits by using additive main effects and multiplicative interactions analysis (AMMI). Additive main effects and multiplicative interactions analysis (AMMI) showed that genotype × environment interactions were found very high for fresh forage yield traits.…”
Section: Discussionmentioning
confidence: 99%
“…Sayar [29] evaluated genotype × environment interactions and stability of twenty common vetch (Vicia sativa L.) genotypes for fresh forage yield traits by using additive main effects and multiplicative interactions analysis (AMMI). Additive main effects and multiplicative interactions analysis (AMMI) showed that genotype × environment interactions were found very high for fresh forage yield traits.…”
Section: Discussionmentioning
confidence: 99%
“…In peas, cluster analysis was shown by Acikgoz et al [19] to be more effective than traditional stability analysis. Sayar [23] succeeded in revealing consistent genotypes in common vetch (Vicia sativa L.). Macák et al [24] reckoned that pea grain yield may be more stable with high fertilizer levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some researchers reported the considerable effects of G, E, and GEI on seed yield of chickpea (Bakhsh et al, 2011;Danyali et al, 2012;Farshadfar et al, 2011Farshadfar et al, , 2013Fikre et al, 2018;Kanouni et al, 2015). In agreement with the high contribution of environmental (E) variation in total variation, other researchers also reported a higher contribution of the environment than the other two components (G and GE) (Bakhsh et al, 2011;Erdemci, 2018;Farshadfar et al, 2011;Kanouni et al, 2015;Pouresmael et al, 2018;Sayar, 2017). The enormous value of environment sum of squares infers that environment has a central role in determining variation for seed yield in dryland cultivation of chickpea in Iran.…”
Section: Discussionmentioning
confidence: 80%